Extracellular matrix and epithelial differentiation of Wilms' tumor. - Sariola, H. (1985)
Different histologic types of 82 Wilms' tumors were graded on the basis of the histologic pattern. Representative tumors of each group were analyzed by the immunoperoxidase method for evaluation of the histogenesis of Wilms' tumor and the value of antibodies against extracellular matrix (ECM) components (collagens I and III, laminin, fibronectin) in differential diagnosis of different types of Wilms' tumors. The tubules of classic Wilms' tumor expressed laminin, which could be seen also in and around some blastemal cells. Blastema and tubules were negative for interstitial collagens, but Type I and III collagen were prominent in the fibrovascular stroma. The monomorphous tubular, psammomatous and rosetting tumors expressed laminin, but no interstitial collagens. In sarcomas, only the blastemal variant of spindle-cell sarcomas was negative for interstitial collagens, which were abundantly seen in all other sarcomas. While spindle-cell sarcomas were devoid of laminin, the highly malignant rhabdoid and clear-cell sarcomas expressed laminin in a characteristic dotted fashion. Staining for fibronectin gave varying results and had therefore only a limited value in distinguishing different types of Wilms' tumors. However, the antibodies against interstitial collagens and against the basement membrane glycoprotein laminin turned out to be a useful adjunct in differential diagnosis and classification, especially of sarcomatoid Wilms' tumors. The basement membrane of normal nephrons is similar to that in tubules of triphasic Wilms' tumor, but the ECM of blastemas is different. This transformed phenotype might represent a maturation arrest of the blastemal cell when compared with the expression of proteins during normal nephrogenesis.